The 'carrot' and 'stick' of integrated offender management: implications for police culture. (20th April 2020) - Cram, Frederick
ABSTRACT: One of the many forms that modern policing takes is 'integrated offender management' (IOM). This involves the police working alongside staff from other agencies, including probation and prison officers and drugs workers, all in a bid to reduce offending by prolific offenders. Some of this work involves traditional policing methods of surveillance, catch and convict (the stick). The novelty for the police lies in the emphasis on drawing offenders away from crime through 'pathway support' such as helping them into employment and supporting them into stable housing arrangements (the carrot). In theory this changes the nature of the policing task considerably. Given the emphasis in the existing literature on how 'cop culture' derives from the nature of the job police officers perform, this raises interesting questions as to whether IOM officers exhibit different cultural traits from their mainstream colleagues. In this article, based on ethnographic fieldwork, I examine whether the operation of IOM, as expressed through officers' talk and action, lives up to its rhetoric of a radical new approach to policing.